Mengelola Keuangan Dalam Usaha Untuk Membantu Perekonomian - Elvina Safitri; Mukhlis Yunus; Hayati Hayati; Suci Nisa Angraini (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Community service looks at business financial management which has not been implemented optimally by business actors. This becomes a problem and instability in running a business. Community service is implemented in four stages. The four stages are related to each other so that solutions can be found to existing problems, including the lack of clarity regarding profit distribution in financial reports, so that financial management is traditional. Community servive was carried out at shop X in Riau Province. The implementation of community service ran smoothly, supported by good cooperation with partners.